Analisis Pengungkapan Corporate Social Responsibility Berdasarkan Global Reporting Initiatives (GRI):Studi Kasus Perusahaan Tambang Batubara Bukit Asam (Persero) Tbk dan Timah (Persero) Tbk. - Sari, Nuraini (Bina Nusantara University, 2014)
This study aims to provide an overview of the disclosure of Corporate Social Responsibility (CSR) in the mining companys corporate sustainability report. It is also to analyze the disclosure of Corporate Social Responsibility (CSR) in corporate sustainability report with standard Global Reporting Initiatives (GRI) 3.1. Research was conducted in Batubara Bukit Asam (Persero) Tbk. and Timah (Persero) Tbk. on their corporatesustainability report for the year of 2012. The analysis was conducted on the presentation of economic performance indicator, environmental performance indicator, performance indicators of employment and workplace practices, human rights performance indicator, public performance indicator and performance indicator reported products liability provisions established in the GRI 3.1. The result is the two companies havedisclosed CSR in accordance with GRI3.1. Batubara Bukit Asam (Persero) Tbk and Timah (Persero) Tbk have disclosed their performance indicators; and the average has exceeded 75%. However, the disclosure of each indicator and its aspects are not comprehensive.